Emergency Medicine Pharmacists and Sepsis Management. (August 2013) - Weant, Kyle A.; Baker, Stephanie N.
Purpose: To describe the role that an emergency medicine (EM) clinical pharmacist has on the management of patients presenting to the emergency department (ED) with sepsis, severe sepsis, or septic shock. Methods: The clinical consultations documented by the EM pharmacists at an academic, teaching hospital over a 2-year period were retrospectively reviewed. Results: During the study period, a total of 585 consultations were provided by the EM pharmacists to 130 patients who presented to the ED with a diagnosis of sepsis, severe sepsis, or septic shock. Dosing recommendations were the most frequent consultations provided (n = 309, 53%), followed by the addition of appropriate empiric antibiotics (n = 131, 22%) and medication preparation (n = 108, 19%). Antibiotics (n = 307, 83%) and vasopressors (n = 31, 8%) were the medication classes regularly involved in EM pharmacist consultations. Vancomycin (n = 90, 28%) and norepinephrine (n = 15, 48%) were the most common agents involved in these consultations. Conclusion: A clinical EM pharmacist has multiple roles in the early management of patients presenting with sepsis, severe sepsis, or septic shock in the ED. Most commonly, they have a role in optimizing empiric antibiotic selection and dosing; thereby ensuring adequate antimicrobial coverage in this complex patient population.